STUDI FAKTOR KANSEI PADA PRODUK BERBASIS KEARIFAN LOKAL (STUDI KASUS: BATIK MALANGAN) - Hardininingtyas, Dewi; Tama, Ishardita Pambudi; Eunike, Agustina; Andriani, Debrina Puspita (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
One product that has a short life cycle is a fashion products where the consumer desires can influence the company's decision to develop the product. Batik is one of Indonesian local wisdom, which not all of batik in Indonesia has a high popularity, such as Batik Malangan. Kansei Engineering method used in this study to identify the implicit desire of users in the form of feeling, emotion, or perception when interacting with Batik Malangan. By implementing the procedures Kansei Engineering Type I, there are 30 words that appear using 14 stimulants of Batik Malangan. Statistical data analysis performed using multivariate analysis. The most important kansei words chosen by using Factor Analysis and Principal Component Analysis. In this study, a total of 61 respondents who are citizens of Malang and from outside Malang participated. For customers, the main attraction at the Batik Malangan is the motive, whether the primary motive, secondary motive, nor the isen motive. Until now, Batik Malangan’s motive not yet have a characteristic, so it is less well known by customers. Overall, this study contributes to that Kansei Engineering is a method that can be used to capture the feeling of customers mainly on customized products. With so many product variations based on local wisdom should be able to be developed by actually capturing the customer's desire, not only explicit but also implicit.